Revealing the role of supernatant and granular sludge fractions on granular anaerobic membrane bioreactor fouling. (October 2022) - Sanchez, Lucie; Lesage, Geoffroy; Demiral, Yasar Onur; Rodriguez-Roda, Ignasi; Heran, Marc; Blandin, Gaetan
Abstract: In order to design efficient fouling mitigation strategies in granular anaerobic membrane bioreactors (G-AnMBR), foulant characteristics and their role have to be thoroughly investigated. Raw mixed liquor of G-AnMBR was split by sieving into granules and supernatant fractions at 0.125 mm. Then, the fouling potential and reversibility of the different samples (granules, supernatant and raw mixed liquor) were assessed by measuring critical fluxes and through filtration tests. Various hydrodynamic conditions, i.e. gas sparging and recirculation, were applied to evaluate the impact of shear stress on fouling propensity. Results revealed that the supernatant fraction, composed of fine compounds and micro-particles, had a strong fouling potential, whilst the granule fraction led to minor fouling filtration resistance. Three-dimensional excitation emission fluorescence spectroscopy emphasised the prominent role of colloidal proteins in G-AnMBR membrane fouling. During the filtration test of raw mixed liquor, the fouling propensity of the micro-particles was lowered, since the structural cake layer was modified. Gas sparging allowed for the mitigation of cake formation, but excess of shear forces may lead to granule break-up and more irreversible fouling. Liquid recirculation led to a higher filtration resistance, but almost all the membrane permeability was recovered by physical cleaning. A short filtration cycle without gas sparging followed by a short period of relaxation and gas sparging could be a suitable fouling mitigation method. In this way, release of micro-particles from granule break-up could be limited, the cake build-up would be mostly reversible by physical cleaning, and the energy demand of gas sparging would be greatly reduced, thereby improving the energy neutrality of the G-AnMBR biotechnology. Graphical abstract: Unlabelled Image Highlights: Granule-shaped sludge had a small fouling potential (≤0.2 mbar·min −1 ). Micro-particles belonging to the supernatant appeared as the main G-AnMBR foulant. Granules partly helped to reduce fouling propensities of supernatant compounds. Moderate gas sparging was the most efficient method in mitigating membrane fouling. Membrane fouling resistance was mostly easily-reversible.